Process‐explicit models reveal pathway to extinction for woolly mammoth using pattern‐oriented validation. (5th November 2021) - Fordham, Damien A.; Brown, Stuart C.; Akçakaya, H. Reşit; Brook, Barry W.; Haythorne, Sean; Manica, Andrea; Shoemaker, Kevin T.; Austin, Jeremy J.; Blonder, Benjamin; Pilowsky, Julia; Rahbek, Carsten; Nogues‐Bravo, David
Abstract: Pathways to extinction start long before the death of the last individual. However, causes of early stage population declines and the susceptibility of small residual populations to extirpation are typically studied in isolation. Using validated process‐explicit models, we disentangle the ecological mechanisms and threats that were integral in the initial decline and later extinction of the woolly mammoth. We show that reconciling ancient DNA data on woolly mammoth population decline with fossil evidence of location and timing of extinction requires process‐explicit models with specific demographic and niche constraints, and a constrained synergy of climatic change and human impacts. Validated models needed humans to hasten climate‐driven population declines by many millennia, and to allow woolly mammoths to persist in mainland Arctic refugia until the mid‐Holocene. Our results show that the role of humans in the extinction dynamics of woolly mammoth began well before the Holocene, exerting lasting effects on the spatial pattern and timing of its range‐wide extinction. Abstract : Reconstructing fossil and ancient DNA evidence of range collapse and extinction of woolly mammoth in Eurasia requires over‐hunting by humans in the Late Pleistocene, and the persistence of woolly mammoth in refugia for thousands of years longer than previously thought. Using macroecological models of climate‐human‐megafauna interactions, we strengthen and better resolve the case for human impact as a crucial and chronic driver of early stage population declines of woolly mammoth, and pinpoint likely locations of yet to be discovered Holocene‐age refugia.